ANALISA DAYA DUKUNG TIANG PANCANG STATIS DAN DINAMIS PADA BENDUNGAN GERAK SEMBAYAT GRESIK - Reno Dwi Santoso; Dwi Kartikasari (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2017)
In general, foundation is defined as the underground building that continues the load from the weight of the building itself and fromthe external load that works at the buildi ng to the ground around it. Carrying capacity analysis of pile is needed to get the planning of foundation that meetsthe requirements. There are many calculation methods used to analyze the carrying capacity of the pile, but it needs to consider which method is more fulfilling from the data in the field, for that, it needs  carrying  capacity  analysis  of  several  methods  based  on  field  data  using  sondir  data  and compared to one another to obtain more realistic results. Capacity analysis method of pile on the construction of Dams Motion in Sembayat Gresik uses static and dynamic methods. In the dynamic method, it use several methods, those are Hiley equation, Wika Method, ENR method, Eytelwein Method, Navy-Mc.Kay Method, and Michigan State Highway of Commission  Method. While in the static  method,  it  uses  Luciano  Dacourt  Method.  From  the  analysis  of  the  static  pile  carrying capacity obtained the result that pile carrying capacity calculation of Luciano Dacourt Method is smaller,  pull Q permitted  15.25 tons and maximum press Q  permitted    41.55 tons compared with the calculation method by using kalendering result of Eytelwein Method. In Eytelwein Method, the minimum pile carrying capacity is 61.566 tons of calculations in GW 1.